Dampak Fintech terhadap Kinerja dan Regulasi Perbankan di Indonesia - Kharismawati, Alfaning Martina (Media Hukum Indonesia (MHI), 2025)
The development of financial technology (fintech) has brought fundamental changes to the global financial services system, including in Indonesia. Fintech offers various innovations that improve efficiency, inclusiveness, and convenience in financial transactions. However, behind these benefits lie major challenges for the banking sector, particularly in terms of data security, regulation, and financial system stability. This study aims to analyze the impact of fintech on banking performance and innovation from a banking law perspective, as well as to examine the readiness of existing regulations in responding to this digital disruption. Through a qualitative approach based on literature review, this study shows that collaboration between banks and fintech companies can be a mutually beneficial strategy, provided it is supported by a strong legal framework, an integrated supervisory system, and optimal consumer protection.